Pulsed Electric Field Treatment Promotes Lipid Extraction on Fresh Oleaginous Yeast Saitozyma podzolica DSM 27192 - Gorte, Olga; Nazarova, Natalja; Papachristou, Ioannis; Wüstner, Rüdiger; Leber, Klaus; Syldatk, Christoph; Ochsenreither, Katrin; Frey, Wolfgang; Silve, Aude (Frontiers in Bioengineering and Biotechnology, 2020)
This study reports on the use of pulsed electric field (PEF) as a pre-treatment step to enhance lipid yield using extraction with ethanol-hexane blend on fresh oleaginous yeast Saitozyma podzolica. The yeasts were cultivated in nitrogen-depleted condition and had a lipid content of 26.4±4.6 % of dry weight. PEF-treatment was applied on the yeast suspension either directly after harvesting (unwashed route) or after a washing step (washed route), which induced a reduction of conductivity by a factor 8. In both cases, cell concentration 20 g of biomass per litre of suspension. In the unwashed route, the lipid yield increased from 7 % (untreated) to 55 % thanks to PEF-treatment. In case an additional washing step was added after PEF-treatment, up to 81 % of the lipid content could be recovered. The washed route was even more efficient since lipid yields increased from 26 % (untreated) to 99 % of total lipid. The energy input for the PEF-treatment never exceeded 150 kJ per litre of initial suspension. The best lipid recovery scenario was obtained using pulses of 1 µs, an electric field of 40 kV/cm and it required slightly less than 11 MJ/kgLIPID. This amount of energy can be further reduced by at least a factor 5 by optimising the treatment and especially by increasing the concentration of the treated biomass. The process can be easily upscaled and does not require any expensive handling of the biomass such as freezing or freeze-drying. These findings demonstrate the potential benefit of PEF-treatment in the downstream processing of oleaginous yeast. From a basic research point of view, the influence of conductivity on PEF energy requirements and extraction yield was examined and results suggest a higher efficiency of PEF-treatment in terms of energy when treatment if performed at lower conductivity.